Notes on calycophyllous Rubiaceae. Part V. A succinct overview of genera with calycophylls, and a revision of Pteridocalyx (Sipaneeae) with observations on distyly and calycophyll variation - Delprete, Piero G. (Phytotaxa, 2019)
The first part of this paper includes a short discussion on calycophylls in Rubiaceae, followed by a succinct overview of calycophyllous genera and their systematic position within the family (subfamilies and tribes). The second part is focused on Pteridocalyx, the sole genus of the tribe Sipaneeae with calycophylls, until recently only known by three historic collections (including two type gatherings) from Guyana. Recent field observations and collection of numerous herbarium specimens permitted a detailed study of this genus, which is here reported for the first time to have distylous flowers. Two species were described in the genus. As a result of a detailed morphological analysis, Pteridocalyx is here treated as monospecific, and is here illustrated for the first time.